2021
DOI: 10.1108/gkmc-12-2020-0193
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, use and attitudes of students towards e-books: differences based on gender, discipline and degree level

Abstract: Purpose The purpose of this study was to explore the level of awareness, use and attitudes of students regarding e-books. Design/methodology/approach This study used a quantitative research design based on the survey method. A structured questionnaire was designed and used for data collection from four different universities of Pakistan. A total of 305 responses were collected from a sample of 400, and 303 of those responses were used for data analysis. Findings The results of this study indicated that stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The most important element is digital mindful leadership, which focuses on human capacity building and up-skilling library professionals through knowledge, experience, training, and education ( Ameen, 2021 ; Ashiq, Rehman, & Mujtaba, 2021 ). Besides, information societies are increasingly demanding information in online and digital formats ( Jbeen et al, 2021 ). Libraries must develop infrastructure and systems to show their online presence, increase access to services, fulfil the demands of remote library users, and most importantly, equip professional librarians with the desired set of skills ( Ashiq et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The most important element is digital mindful leadership, which focuses on human capacity building and up-skilling library professionals through knowledge, experience, training, and education ( Ameen, 2021 ; Ashiq, Rehman, & Mujtaba, 2021 ). Besides, information societies are increasingly demanding information in online and digital formats ( Jbeen et al, 2021 ). Libraries must develop infrastructure and systems to show their online presence, increase access to services, fulfil the demands of remote library users, and most importantly, equip professional librarians with the desired set of skills ( Ashiq et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, where learning is mandatory, professionals are finding e-courses attractive as these learning platforms use engaging teaching tactics, have well-designed learning materials, offer rapid and constructive feedback and also offer social recognition to motivate learners to complete tasks. Jbeen et al (2022) suggested that learners already prefer to use e-books and had a favourable opinion finding them very simple and helpful.…”
Section: Perceived Usefulness Of E-learning For Working Professionalsmentioning
confidence: 99%
“…Internet Experience is another important factor that was investigated in [ 39 , 54 , 59 , 60 , 61 , 62 , 63 ]. Hence the following hypothesis was postulated.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Education level is an important factor that influenced behavioral intention in previous studies [ 54 , 59 , 64 , 65 ]. Hence the following hypothesis was postulated.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation